Spatial Clustering for Narcotics-Related Arrests in Malaysia - Rahim, ‘Ulya Abdul; Tajuddin, Razik Ridzuan Mohd; Wei, Lim Choong; Nordin, Ahmad Azwan Amin; Kassim , Mohammad; Firdaus-Raih, Mohd (Journal of Quality Measurement and Analysis, 2026)
Malaysia’s proximity to the Golden Triangle has made it highly susceptible to narcotics crimes. Thus, the purpose of this research is to identify the spatial clustering and the hot spots of narcotics-related offences – distribution, possession, and positive urine. Using over 100,000 arrest records obtained from the Royal Malaysia Police for the year 2022, spatial autocorrelation was analyzed using Moran’s and Getis-Ord . The results indicated significant positive spatial autocorrelation for all three offences, and among them, the distribution offences tended to cluster more than the other two offences. Furthermore, the hot spots for the distribution and possession offences were concentrated in the northern as well as central regions of Peninsular Malaysia, while the hotspots for positive urine offences were primarily located in the east coast region of Peninsular Malaysia. Sabah and Sarawak exhibited weak or insignificant clustering, suggesting limited spatial concentration of arrests for all three offences. These findings highlight the need for geographically targeted enforcement strategies and provide spatial intelligence that supports data-driven decision-making in narcotics prevention and rehabilitation policy planning.